Strategi Pengelolaan Usaha Mikro Kecil dan Menengah Olah Bebaya Separi dalam Memasuki Pasar Modern - Zulkarnain; Ekklesia Hendra Pratama (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2021)
This study aims to determine the management strategy of SMEs in entering the modern market and the obstacles faced by SMEs in Bebaya Separi. The method used in this research is qualitative with ten informants. Data was collected using observation, interview and documentation techniques. The results obtained in this study indicate that the MSME Processing Bebaya Separi uses fresh flat fish to maintain the image of the taste of its products, provides two types of prices, namely Rp. 5,0000, - and Rp. 125,000,-. and do more promotion using social media. The obstacles faced include capital constraints and obstacles in the training of making Amplang for the MSME managers. Keywords: Strategy, MSME, Modern Market